2021
DOI: 10.1182/blood.2020006610
|View full text |Cite
|
Sign up to set email alerts
|

miR-130b and miR-128a are essential lineage-specific codrivers of t(4;11) MLL-AF4 acute leukemia

Abstract: t(4;11) MLL-AF4 acute leukemia is one of the most aggressive malignancies in the infant and pediatric population, yet we have little information on the molecular mechanisms responsible for disease progression. This impairs the development of therapeutic regimens that can address the aggressive phenotype and lineage plasticity of MLL-AF4-driven leukemogenesis. This study highlights novel mechanisms of disease development by focusing on two microRNAs upregulated in leukemic blasts from primary patient samples: m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…Upregulation of 130b has been implicated in T-ALL occurrence, especially in TAL -r T-ALL pediatric cases [ 10 , 28 ]. This miRNA has been associated with drug resistance, and it is an essential driver of KMT2A - AFF1 leukemia, integrated with the aberrant overexpression of key downstream targets, i.e., the antiapoptotic factor BCL2 and proto-oncogene MYC [ 195 , 196 ]. The role of miR-146a in childhood ALL is discussed above in the text.…”
Section: Resultsmentioning
confidence: 99%
“…Upregulation of 130b has been implicated in T-ALL occurrence, especially in TAL -r T-ALL pediatric cases [ 10 , 28 ]. This miRNA has been associated with drug resistance, and it is an essential driver of KMT2A - AFF1 leukemia, integrated with the aberrant overexpression of key downstream targets, i.e., the antiapoptotic factor BCL2 and proto-oncogene MYC [ 195 , 196 ]. The role of miR-146a in childhood ALL is discussed above in the text.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, we identified miR-130b as being downregulated by IK1 induction. miR-130b is highly expressed in B-ALL [69], including the poor prognosis subgroup of MLL-AF4 Acute leukemia, and mechanistic studies have explored miR-130b as an oncomiR in other cancers, such as colorectal and lung cancer [50,62,70,71]. It has been suggested that miR-130b regulates growth arrest in B-lymphoid differentiation, and these mechanisms contribute to the direct downregulation of tumor suppressor genes NR2F6 and SGMS1 in MLL-rearranged leukemia [71].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, any truly representative model of infant leukaemia should demonstrate the typical leptomeningeal leukaemic infiltrate seen in patients (Price and Johnson, 1973). The above described Mll-AF4 + VEC-Cre + miR-128 + and/or miR-130b + overexpression models of infant leukaemia (Malouf et al, 2021) demonstrate this typical CNS disease pattern. Both miRNAs drive different lineages of leukaemia, with leptomeningeal leukaemia infiltrate present to a more significant extent in the pro-B ALL driven by miR-128a overexpression compared with the mixed/ B-cell precursor/myeloid lineage acute leukaemia driven by miR-130b overexpression.…”
Section: Placenta and Central Nervous System As Other Specialised Nichesmentioning
confidence: 91%
“…Indeed, we recently resolved this by identifying two microRNAs (miRNAs), i.e. miR-128a and miR-130b, that are upregulated in human MLL-AF4 infant and paediatric leukaemia patient samples but not in the Mll-AF4 + VEC-Cre + mouse model ( Malouf et al, 2021 ). By overexpressing these miRNAs individually in foetal liver Lineage − Sca1 + cKit + (LSK) cells during the E12-14 pre-leukaemic window, we were able to induce miRNA-dependent lineage-specific acute leukaemias that accurately replicate the spectrum of MLL-AF4 infant leukaemia phenotypes ( Fig.…”
Section: Aspects Of Niche Involvement In Infant Leukaemiamentioning
confidence: 99%